(untitled) (CIPEEX, 2025)
Introduction: Fibromyalgia is a type of rheumatic syndrome of still unknown origin, with musculoskeletal pain as its main characteristic. Its prevalence in the general population is 2%. In Brazil, fibromyalgia is one of the most frequent rheumatological diseases after osteoarthritis, with a prevalence of 2.5% of the population. However, resistance exercises have proven to be an excellent strategy for the treatment of fibromyalgia. Objectives: To analyze the effects of resistance training on pain levels in individuals with fibromyalgia. Methods: For this purpose, a bibliographic review was conducted on the topic of studies published until December 2023, in the MEDLINE/PubMed, ISI Web of Knowledge, and Scopus databases using the following English descriptors: "Resistance Training AND Fibromyalgia". Results: After the search, studies that met the eligibility criteria were selected. After analysis, 8 chronic intervention studies were included. Conclusion: Resistance training reduces pain in patients with fibromyalgia from the 8th week of training onwards, provided it is performed continuously, in a guided and progressive manner.